We just moved! - Krensky, Stephen (New York : Scholastic Inc, 1998)
When a boy moves with his family to a bigger castle, he finds that some things about life in the new place are different, some things are the same, and he gets more comfortable the longer he is there.
Keywords: Moving, Household - Fiction; Castles - Fiction; Middle Ages - Fiction